2019
DOI: 10.5114/aoms.2019.81729
|View full text |Cite|
|
Sign up to set email alerts
|

Antitumor and apoptotic effects of 5-methoxypsoralen in U87MG human glioma cells and its effect on cell cycle, autophagy and PI3K/Akt signaling pathway

Abstract: IntroductionThe main purpose of the current study was to investigate the antitumor effects of 5-methoxypsoralen in U87MG human glioma cells along with studying its effects on cell cycle progression, autophagy and the PI3K/Akt signaling pathway.Material and methodsThe cytotoxic effects of the drug were demonstrated by the MTS cell viability assay while its effects on cellular morphology associated with cell apoptosis were evaluated by phase contrast and fluorescence microscopic techniques. Effects of 5-methoxyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 18 publications
3
18
0
Order By: Relevance
“…In addition, Ferraroni (10) synthesized a series of Coumarins and corresponding 2-thioxocoumarines and tested their inhibitory activities to human carbonic anhydrase CA I, CA II, CA IX, and CA XII, and found that 7-[(1-Phenyl-1H-1,2,3-triazol-4-yl) methoxy]-2H-chromen-2-one (15) and 7-[(1-phenyl-1H-1,2,3triazol-4-yl)methoxy]-2H-chromene-2-thione (16) was the most effective and the selective inhibitors of CA IX and CA XII, with the Kis are comparable to or slightly lower than the standard sulfonamide AAZ. To explore the inhibitory mechanism of 2thioxocoumarin to CA, Ferraroni (10) examined the X-ray crystal structure of 6-hydroxy-2-thioxocoumarin which bound to CA II and found that the inhibitory mechanism of 2-thioxocoumarin is quite different from other coumarins, which work as zinc binders or occlusion of the active site entrance, anchor to the metal-ioncoordinated water/hydroxide ion, or bind to outside of the active sites, then hydrolyzed by CA, finally form the corresponding 2hydroxycinnamic acid derivatives.…”
Section: Anticancer Mechanisms Coumarins Act As Ca Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Ferraroni (10) synthesized a series of Coumarins and corresponding 2-thioxocoumarines and tested their inhibitory activities to human carbonic anhydrase CA I, CA II, CA IX, and CA XII, and found that 7-[(1-Phenyl-1H-1,2,3-triazol-4-yl) methoxy]-2H-chromen-2-one (15) and 7-[(1-phenyl-1H-1,2,3triazol-4-yl)methoxy]-2H-chromene-2-thione (16) was the most effective and the selective inhibitors of CA IX and CA XII, with the Kis are comparable to or slightly lower than the standard sulfonamide AAZ. To explore the inhibitory mechanism of 2thioxocoumarin to CA, Ferraroni (10) examined the X-ray crystal structure of 6-hydroxy-2-thioxocoumarin which bound to CA II and found that the inhibitory mechanism of 2-thioxocoumarin is quite different from other coumarins, which work as zinc binders or occlusion of the active site entrance, anchor to the metal-ioncoordinated water/hydroxide ion, or bind to outside of the active sites, then hydrolyzed by CA, finally form the corresponding 2hydroxycinnamic acid derivatives.…”
Section: Anticancer Mechanisms Coumarins Act As Ca Inhibitorsmentioning
confidence: 99%
“…5-methoxypsoralen, also known as bergamot and parsley alkali, is a natural product of furocoumarins and usually isolated from psoralen. Guo (16) found that 5-methoxypsoralen inhibits the expression and phosphorylation of PI3K, Akt, and mTOR in human glioma cells, thereby completely down-regulating the expression and activation of the PI3K/Akt/mTOR signaling pathway. 5-methoxypsoralen can also cause DNA damage by fragment the DNA of human glioma cells, and induce the appearance of autophagy vacuoles.…”
Section: Coumarins Can Inhibit Pi3k/akt/mtor Signaling Pathwaymentioning
confidence: 99%
“…Therefore, chondrocyte clusters can induce calcification in the cartilage matrix a well as the growth and proliferation of chondrocytes, and the activity of chondrocyte clusters is associated with the death of chondrocytes and the generation of apoptotic bodies [4,5]. Moreover, apoptosis is also an important index for the treatment of various diseases via different durgs [6][7][8][9][10]. For example, etanercept could protect ovarian reserve against ischemia-reperfusion injury (IRI) via regulating apoptosis [7], eriodictyol exerted its anticancer activity through induction of mitochondrial apoptosis in the treatment of lung cancer [8], and salvianolic acid A had a synergistically protective effect on hepatic IRI via hepatocellular apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, etanercept could protect ovarian reserve against ischemia-reperfusion injury (IRI) via regulating apoptosis [7], eriodictyol exerted its anticancer activity through induction of mitochondrial apoptosis in the treatment of lung cancer [8], and salvianolic acid A had a synergistically protective effect on hepatic IRI via hepatocellular apoptosis. Moreover, 5methoxypsoralen could exert apoptotic effects in U-87MG human glioma cells [9] and glucose fluctuation could also increase mesangial cell apoptosis [10].…”
Section: Introductionmentioning
confidence: 99%
“…T24 cells exhibit typical morphology of apoptosis after treatment with ISL, including nuclear shrinkage, nuclear fragmentation, chromosome edge set, etc. It is speculated that the anti-tumor mechanism of ISL might be associated with the increase of CDK2 viability, the down-regulation of inner mitochondrial membrane potential (DeltaPsim), and activation of the caspase-3/9-mediated mitochondrial apoptotic signaling pathway [15][16][17][18], but the specific molecular mechanism of ISL in cancer treatment remains unclear.…”
Section: Introductionmentioning
confidence: 99%